Decolonizing nature/knowledge: indigenous environmental thought and feminist praxis - Nosheen Ali; Binish Samnani; Abdul Wali Khan; Najmi Khatoon; Barkat Ali; Sadia Asfundyar; Muhammad Aslam; Sumaira Amirali (University of Johannesburg, 2019)
This faculty-student collaborative article is a result of a graduate seminar on 'Environmental Education' taught at the Aga Khan University's Institute for Educational Development in Karachi, and it illuminates new perspectives and pedagogies of nature from the global South, specifically South Asia. Drawing inspiration from feminist and indigenous thought, the narratives of ecology shared here center the place of emotions, experience, memory and spiritual intimacy, offering one means of decolonizing environmental studies and expanding our understanding of 'environmental consciousness'. These narratives defy ontologies of nature-human separation, capturing not just the co-existence of animals, spirits and humans but their co-constitution. Such indigenous ecologies of knowledge and wisdom, we argue, offer a timely corrective to fragmented and exploitative constructions of the natural environment as mere resource, pleasure, or commodity, while providing a profound, alternative basis for a richly layered, spirited, environmental education. How to cite this article: ALI, Nosheen; SAMNANI, Binish; WALI KHAN, Abdul; KHATOON, Najmi; ALI, Barkat; ASFUNDYAR, Sadia; ASLAM, Muhammad; AMIRALI, Sumaira. Decolonizing nature/knowledge: indigenous environmental thought and feminist praxis. Scholarship of Teaching and Learning in the South. v. 3, n. 1, p. 77-91, Apr. 2019. Available at: https://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=80&path%5B%5D=36 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/